GIANT OVARIAN CYST IN TERM PREGNANCY - A rare case report - Hota, Basanta Manjari; Rukmini, K. Radha; Basavaih, Prabhakar Gowdar Channa (BALI MEDICAL JOURNAL, 2015)
Ovarian cyst in pregnancy may have a poor feto-maternal outcome. A 25 year old multi gravida, post caesarean pregnancy at term reported with antenatal ultrasonography (USG) diagnosis of giant unilocular ovarian cyst and normal obstetrics findings. Elective lower segment caesarean section (LSCS) with left salpingo-oophorectomy and right partial salpingectomy was done. Left ovarian cyst was 29x20 cm in size with smooth surface, no adhesion, no free fluid in peritoneal cavity and a normal right ovary. Histopathological examination revealed mucinous cystadenoma of ovary. Post-operative period was uneventful. The rarity of the case and its successful management prompted us for reporting along with review of literatures.
Keywords: Mucinous cystadenoma, pregnancy.